The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1177/0014402915598782
|View full text |Cite
|
Sign up to set email alerts
|

Envisioning the Future of Special Education Personnel Preparation in a Standards-Based Era

Abstract: The authors consider the future of special education personnel preparation by responding to an overarching question: What frameworks might teacher educators use as a basis to promote special education teacher effective performance now and in the future? In answering this question, they summarize current trends in the context of schooling and special education (i.e., Common Core State Standards [CCSS], multi-tiered systems of support [MTSS]) and what these contexts demand of special education teachers. The auth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
133
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 70 publications
1
133
0
Order By: Relevance
“…Parent involvement and interagency collaboration are also required components of transition planning under IDEA and are Despite these requirements, which have been found to improve student outcomes , IDEA regulations are generally vague in nature, leaving educators, students, families and service providers feeling unsure how to help students achieve positive post-school outcomes (Francis et al, 2014;US GAO, 2012). Further, there remains a lack of research on the efficacy of transition strategies and best practices across the globe (Ellerbrock et al, 2015;Leko et al, 2015;Pallisera et al, 2014;Richardson et al, 2017). In particular, young adults with disabilities commonly require ongoing and sometimes intensive support from parents and other family members (Rupp & Ressler, 2009), and the expectations and actions of parents are found to profoundly influence young adult outcomes (Mann et al, 2016).…”
mentioning
confidence: 99%
“…Parent involvement and interagency collaboration are also required components of transition planning under IDEA and are Despite these requirements, which have been found to improve student outcomes , IDEA regulations are generally vague in nature, leaving educators, students, families and service providers feeling unsure how to help students achieve positive post-school outcomes (Francis et al, 2014;US GAO, 2012). Further, there remains a lack of research on the efficacy of transition strategies and best practices across the globe (Ellerbrock et al, 2015;Leko et al, 2015;Pallisera et al, 2014;Richardson et al, 2017). In particular, young adults with disabilities commonly require ongoing and sometimes intensive support from parents and other family members (Rupp & Ressler, 2009), and the expectations and actions of parents are found to profoundly influence young adult outcomes (Mann et al, 2016).…”
mentioning
confidence: 99%
“…We need to ensure that PD for both PSTs and ISTs provides sufficient focus on DBI‐related knowledge and mentored support in developing expertise in designing and implementing DBI with students. For PSTs, there is emerging guidance about effective practice in training reading content knowledge to support DBI (e.g., Alsopp et al., ; Leko, Brownell, Sindelar, & Kiely, ). This research is reflected in the Knowledge and Practice Standards , which the International Dyslexia Association has developed to guide teacher preparation (Moats et al., ).…”
Section: Implications and Next Stepsmentioning
confidence: 99%
“…Additionally, Leko et al. () proposed a framework for university faculty training PSTs to ensure that there is a carefully designed sequence of coursework and fieldwork that includes multiple opportunities to receive expert feedback and to reflect on (or self‐assess) the efficacy of their instruction through supported practice activities (e.g., structured tutoring, clinical field experiences, peer coaching, lesson study, and coaching via technology). The need to ensure clinical field experiences are meaningful and provide PSTs with opportunities to apply evidence‐based practices is also part of the National Council of Accreditation for Teacher Education (NCATE, ) standards for teacher education.…”
Section: Implications and Next Stepsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although students with special needs have been placed in general education classrooms for many years, numerous studies have suggested that many general education teachers are not fully aware of what needs to happen to make the inclusive setting a successful environment (Bruggnick, Goel, & Koot, 2015;Leko, Brownell, Sindelar, & Kiely, 2015;Smit & Humpert, 2012). Teacher preparation programs (TPPs) and professional development (PD) can provide educators with skills to create opportunities for all students to learn.…”
Section: Introductionmentioning
confidence: 99%